Nearly complete oxidation of Au(0) in hydrophobized nanoparticles to Au(3+) ions by N-bromosuccinimide - Singh, Sanjay; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2007)
Au degrees atoms in hydrophobized gold nanoparticles were oxidized to Au(3+) ions, nearly quantitatively, simply by treatment with N-bromosuccinimide and sonication. (1)H NMR results indicate that the octadecylamine molecules are detached from the Au degrees surface by NBS. The bromine molecules released by NBS are suggested to be the species responsible for the oxidation of Au degrees to Au(3+), which is supported by the observation that addition of molecular bromine also leads to similar results. A gratifying feature is that the Au(3+) ions could be subsequently reduced back to An nanoparticles.